2010
DOI: 10.1097/mlr.0b013e3181de9e17
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Modeling Using EHR Data

Abstract: Heart failure was predicted more than 6 months before clinical diagnosis, with AUC of about 0.76, using logistic regression and Boosting. These results were achieved even with strict model selection criteria. SVM had the poorest performance, possibly because of imbalanced data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(100 citation statements)
references
References 7 publications
1
99
0
Order By: Relevance
“…Data-driven modelling has both practical and theoretical advantages over conventional survival modelling [5, 24]. It may require less user input, through automated variable selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-driven modelling has both practical and theoretical advantages over conventional survival modelling [5, 24]. It may require less user input, through automated variable selection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used machine learning on EHR data for tasks such as patient classification and diagnosis [2224] or predicting future hospitalisation [25], but we are unaware of any systematic comparison of machine learning methods for predicting all-cause mortality in a large, richly characterised EHR cohort of patients with stable coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al, comparing the performance of logistic regression, boosting, and support vector machines to predict the subsequent development of HF, found that the former two methods had comparable performance, while the latter method had the poorest performance [34]. Maroco et al, compared ten different classifiers for predicting the evolution of mild cognitive impairment to dementia [35].…”
Section: Discussionmentioning
confidence: 99%
“…EHR data are routinely collected for all patients at admission, and many studies have used them for prediction of health outcomes during and after the hospital stay (14). Previous works that have used EHR data for delirium prediction, have mainly used multivariate regression models due to their ease of interpretation and analysis (12, 13).…”
Section: Introductionmentioning
confidence: 99%